Wideband Circular Polarized Dielectric Resonator Antenna Array for Millimeter-Wave Applications - Arun Kesavan (Sensors, 2021)
A novel circular polarized dielectric antenna array (DRA) for millimeter-wave applications at 30 GHz is presented in this paper. The unit element array is a flower-shaped DRA fed with a cross slot. To obtain circular polarization, a sequential network combined with the cross slots is used to feed the <semantics>2×2</semantics> array. The prototype of the proposed antenna array is fabricated and measured to obtain a wide resonance bandwidth from 27 GHz to 38 GHz frequency band. Furthermore, this left-hand polarized antenna array has achieved a peak gain of 9.5 dBi with 3-dB axial ratio at 30 GHz. The proposed DRA array with wideband resonance and gain bandwidth has the potential to be used for millimeter-wave wireless communications at the 30 GHz band.